Factors affecting the severity of RH Incompatibility newborn - Anfal akram Hasan; Mohammed Ahmed Jassim Alogaidi; Areej Ali Abbood (Indian Journal of Forensic Medicine & Toxicology, 2021)
Rh incompatibility is a not common pediatric problem, that cause morbidity and mortality in children, and it is an important cause of hemolysis, anemia and jaundice in newborn. To study Rhesus hemolytic disease, its severity, its complications; to evaluate if ABO incompatibility is protective or not, so to find out the efficacy of anti-D globulin ; to evaluate the efficacy of phototherapy and exchange transfusion as a treatment. This study was done on neonates with jaundice, seventy five patients (1-10 days old) who had Rh incompatibility were studied during period from the first of January 2008 to the 30th of June 2008. History was taken about age, gender and gestational age of the patients, determination of gestational age and hepatosplenomegally as a cause of extramedullary hematopoiesis. Investigations done for patients were hemoglobin, total serum bilirubin, reticulocyte count, blood group and Rh, and direct coombs test. From 75 patients studied, 55 patients (73%) required treatment for jaundice;25 of them (46%) required only phototherapy due to mild degree of hemolysis, and 30 of them (54%) required exchange transfusion with phototherapy due to severe degree of hemolytic. The remaining 20 patients (27%) required observation alone. Family history of previous hemolysis was positive in 44 patients and it was a risk factor for having hemolysis in present pregnancy. Early evaluation of patients for jaundice was useful in early recovery. ABO incompatibility in association with Rh incompatibility was not necessarily protective against hemolysis. The administration of anti-D globulin to the mother within first 72 hours after delivery was protective against sensitization. Early and proper management of of Rh incompatibility may reduce need for exchange transfusion. ABO incompatibility was not necessarily protective against hemolysis. Anti-D globulin administered to mothers within 3 days after delivery was protective against sensitization, History of hemolytic in previous siblings is considered as a risk factor for present hemolytic in neonates with Rh incompatibility.